The Effect of Leadership and Motivation on Employee Performance - Purnomo, Yudiyanto; Solihin, Jajang (Jurnal Ilmiah Manajemen Kesatuan, 2023)
The impact of the Covid-19 pandemic has caused tremendous developments in information technology so that all human activity needs are replaced by technology. Information technology can limit human activities so that activities can continue even though they are limited by government regulations, namely lockdown. As information technology develops, higher education institutions change bureaucratic systems to make it easier to control and develop the institutions they lead. Leadership Style: Changes in information technology and bureaucracy influence the success of a leader. Ability to motivate and improve the performance of its members towards superior institutional performance. The aim of this research is to find out how much influence and how leadership and motivation have on employee performance at the ITB Finance Directorate in Bandung City, West Java. This research methodology uses multiple linear descriptive and associative research. Analysis unit of the ITB Finance Directorate in Bandung City, West Java. The population is 36 permanent employees at the ITB Finance Directorate in Bandung City, West Java. The sampling technique used a census of 36 permanent employees at the ITB Finance Directorate in Bandung City, West Java. Descriptive research findings: leadership variables in the scoring category are very good, motivation variables in the scoring category are very good, employee performance variables in the scoring category are very good. Multiple linear associative research leadership variables influence employee performance by 0.857; The motivation variable influences employee performance by 0.655 and the influence of leadership and motivation on employee performance at the ITB Finance Directorate in Bandung City, West Java, amounts to 7,995.